Bullies, Victims and Provocative Victims in Context: Discriminant Factors in a Portuguese Adolescent Sample - Carvalho, Marina; Branquinho, Catia; de Matos, Margarida Gaspar (European Scientific Journal, ESJ, 2017)
Context: With strong and serious impacts on health and individual well-being, bullying presents itself as one of the most traumatic experiences at school age. Objective: analyse the differences between bullies, victims and provocative-victims for individual, relational, school and contextual factors. Design: cross-sectional study based on the 2014 Health Behaviour in School-aged Children study. Results: Bullies reported consuming more tobacco and drugs, but less alcohol, when compared to victims and provocative-victims. Bullies also reported being more involved and having more security feelings at school, better relationships with their peers, being better accepted by the peers, and more positive attitudes, compared to victims and provocative-victims; which reported more fear, sadness, rejection feelings, and also, more withdrawal at school. Group differences were also found in the time spent with friends in everyday life, nigh outs and well-being, with bullies presenting the higher odds. Provocative-victims reported involving more in fights than victims. Otherwise, bullies reported making friends more easily and spending more time with friends after school. Conclusions: Given the different characteristics and impacts of bullying on victims, bullies and provocative-victims, it is essential to consider the interrelations of groups and focus on a more engaging perspective, based on an ecological intervention model. A strong argument is also made related to the need to include young people participation in the definition of public policies to prevent peer related violence, as well as a need to focus not only in the prevention of peer related violence, but also to focus on violence-free, positive relationships